Sex Chromosome Complement and gonadal steroid influences in the sexually dimorphic angiotensinergic and vasopressinergic systems. - Vivas, Laura (2017)
Fil: Vivas, Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigación Médica Mercedes y Martín Ferreyra; Argentina.